Ashraf Mohammed Attia (Journal of Oriental Studies, 2016)
One of the key concepts of cognitive linguistics, our time is the concept of freedom. The concept of freedom with the semanticcognitiveperspective has undergone in recent years, major changes related to psychological and mental orientations of carriers ofdifferent cultures, which has expanded its semantic and syntactic features. In this paper we attempt to analyze the linguistic means bywhich introduced the concept of freedom in the minds of Russian and Arabic.